Proceedings of the 9th International Conference on Neural Information Processing, 2002. ICONIP '02.
DOI: 10.1109/iconip.2002.1202121
|View full text |Cite
|
Sign up to set email alerts
|

Neural networks based identification of helicopter dynamics using flight data

Abstract: In this paper, identification of lateral and longitudinal dynamics of helicopter using flight data is presented. Neural networks with linear filter also known as Narendra's model and recurrent neural networks with intemal memory (Memory Neuron Networks) are used for the purpose. These networks are used for identifying the rate and attitude response of the helicopter to a given longitudinal cyclic and lateral cyclic inputs. The relative effectiveness of these algorithms has been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…For this reason NARX networks were trained using the real sensor data. Their performances are superior compared not only to the linear ones, but also compared to the performances obtained in studies by Suresh et al and San Martin et al 20,29 The drawback in the case of this kind of model is that no model-based control algorithms can be implemented. But, since one of the purposes of the research project is to design a predictive controller based on neural models, the results obtained at this point are promising.…”
Section: Discussionmentioning
confidence: 83%
“…For this reason NARX networks were trained using the real sensor data. Their performances are superior compared not only to the linear ones, but also compared to the performances obtained in studies by Suresh et al and San Martin et al 20,29 The drawback in the case of this kind of model is that no model-based control algorithms can be implemented. But, since one of the purposes of the research project is to design a predictive controller based on neural models, the results obtained at this point are promising.…”
Section: Discussionmentioning
confidence: 83%
“…ϬӴඣՈᴎˊᓎᮍ⊩ [2] ᓎএָछᴎՈӓ‫ף‬ൟᰃৃ ᜐՈˈԚᰃẝᮍ⊩◄ᡅा⇨ᄺ‫ک‬ˈ◄ᡅₓՈ⇨ ᭄ᴹᓎএ⇨ி᭄ǃ⇨ᇐ᭄ൟDŽ໐ϨᮟເႮḰ ┊ẋᶤѯĽ⅞ᜐᚙ‫މ‬ϟˈẝѯ⇨᭄ᰃϡৃᑨ ϬՈDŽℸẝѯᚙ‫މ‬ϟˈᴎˊᓎᮍ⊩Т᮴⊩ᓎএָ छᴎӓ‫ף‬ൟDŽϵѢࠢඓตච‫‬᳝ᄳདՈ☢ඃᗻᇘ࿁ˈ ᆊႮ✊ᄺₕ-ֲ˄ᰈো˖60474069˅ ℸৃҹᑨϬࠢඓตචᓎএָछᴎՈӓ‫ף‬ൟDŽSuresh [3] ߚ߿ϬᏺඃᗻⒸ⊶ᩴᖚऩ‫ܗ‬ՈࠢඓตචᓎএָछᴎՈ ῾൹ᄺൟˈҹቻᕫợᑺ࿓ᗕᇍ῾൹਼ᳳব ‫ڭ‬ՈડᑨDŽSaleh Zein-Sabatto [4] …”
Section: ѣᬃᣕₓᴎոָछᴎᮟເⴎḱ┊ẋᓎunclassified
“…In [19], neural networks with linear filter also known as Narendra's model and recurrent neural networks with internal memory (Memory Neuron Networks) are used for the purpose. From the simulation studies it is shown that MNN approach is better than Narendra's approach.…”
Section: Introductionmentioning
confidence: 99%